A tale of two cities: The genetic mechanisms governing calvarial bone development. Issue 1 (3rd October 2018) - Ferguson, James W.; Atit, Radhika P.
Summary: The skull bones must grow in a coordinated, three‐dimensional manner to coalesce and form the head and face. Mammalian skull bones have a dual embryonic origin from cranial neural crest cells (CNCC) and paraxial mesoderm (PM) and ossify through intramembranous ossification. The calvarial bones, the bones of the cranium which cover the brain, are derived from the supraorbital arch (SOA) region mesenchyme. The SOA is the site of frontal and parietal bone morphogenesis and primary center of ossification. The objective of this review is to frame our current in vivo understanding of the morphogenesis of the calvarial bones and the gene networks regulating calvarial bone initiation in the SOA mesenchyme.